2019
DOI: 10.1142/s266131821950004x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Infertility: The Evidence

Abstract: Vitamin D is a lipid soluble vitamin synthesized by the skin upon exposure to UV light. Approximately 10–20% of vitamin D comes from dietary sources and 25OH-D is its circulating form. Vitamin D receptors are found in reproductive tissues including ovary, uterus, and endometrium permitting investigators to hypothesize a role for vitamin D in reproduction. Indeed, a number of animal studies provide evidence of vitamin D’s importance in fertility. Studies in humans, however, generally have not supported an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…One study has reported that vitamin D status was associated with pregnancy outcomes in women undergoing ART, and women with adequate vitamin D levels had a higher live birth rate after ART than those whose vitamin D levels were defined as deficient or insufficient (odds ratio 1.33, 95% confidence interval 1.08-1.65) (Chu et al, 2018). In contrast, other data provided conflicting evidence (Hornstein, 2019). Our finding that vitamin D status had no impact on ongoing pregnancy rates is consistent with a number of previous studies (Fabris et al, 2014;Franasiak et al, 2015;van de Vijver et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has reported that vitamin D status was associated with pregnancy outcomes in women undergoing ART, and women with adequate vitamin D levels had a higher live birth rate after ART than those whose vitamin D levels were defined as deficient or insufficient (odds ratio 1.33, 95% confidence interval 1.08-1.65) (Chu et al, 2018). In contrast, other data provided conflicting evidence (Hornstein, 2019). Our finding that vitamin D status had no impact on ongoing pregnancy rates is consistent with a number of previous studies (Fabris et al, 2014;Franasiak et al, 2015;van de Vijver et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the potential impact on implantation, vitamin D might play an important role in determining the outcomes of assisted reproductive technology (ART) treatment, especially given that the rate of vitamin D deficiency in individuals of reproductive age is high (Chu et al, 2018;Gordon et al, 2004;Sullivan et al, 2005;Tangpricha et al, 2002). However, the effects of vitamin D levels on ART outcomes are not well understood (Hornstein, 2019). Recent evidence suggests that women with adequate vitamin D levels might have higher clinical pregnancy and live birth rates (Chu et al, 2018;Zhao et al, 2018), while earlier studies found no impact of vitamin D levels on ART outcomes (Aleyasin et al, 2011;Anifandis et al, 2010;Fabris et al, 2014;Firouzabadi et al, 2014;Franasiak et al, 2015;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with CIDR + gr produced a significantly greater P4 peak compared to CIDR gr starting on the 7th, 9th, 11th, 13th, and 15th days through the experiment. This obtained findings about the greater P4 concentrations in CIDR + gr than in CIDR gr could be explained that vitamin D plays a role in reproduction due to vitamin D receptors were found in the ovary, uterus, and endometrium ( Muscogiuri et al, 2017 ; Hornstein, 2019 ) and it increases the secretion of ovarian P4 secretion through the stimulation of 3β-HSD expression in ovary granulosa cells ( Muscogiuri et al, 2017 ; Farahavar et al, 2020 ).…”
Section: Resultsmentioning
confidence: 82%
“…The precise role of vitamin D is the regulation of calcium and phosphorus metabolism. Recently it is been reported that vitamin D plays a role in reproduction as there are vitamin D receptors in female reproductive organs such as ovaries, uterus, and endometrium ( Muscogiuri et al ., 2017 ; Hornstein, 2019 ). Also, phosphorus deficiency causes irregular estrus and anestrus and decreases the production of ovarian follicles which in turn decreases fertility and conception rate ( Ahuja and Parmar, 2017 , Muscogiuri et al ., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings can postulate that VD supplementation is unlikely to improve AMH production. As proposed by various molecular characterization studies, VD receptor polymorphism did not lead to subfertility [20][21]. Hence, labelling VDD as a cause of subfertility is unjustifiable.…”
Section: Discussionmentioning
confidence: 88%